Ethnic Entrepreneurship Adaptation Models: to the Amshen Armenians of the Great Sochi Agglomeration Ethnic History - A. N. Sadovoy (Научный диалог)
Amshen Armenians of the Black sea coast of the Caucasus ethnic entrepreneurship models are the object of study. The relevance of the development is determined by the need to study: a) the ethnic structure of the population of the South of Russia the formation of history and genesis; b) the system of interethnic communication at certain stages of historical development. The analysis of the phenomenon of ethnic entrepreneurship and its local manifestations is carried out on the basis of historiographical sources and field research materials. The author focuses on the problems of allocation of adaptive models of entrepreneurship, the Genesis of this phenomenon and the nature of its impact on the system of intra - and inter-ethnic communications. The problem of interrelation between entrepreneurial activity and preservation of traditional economic specialization and ethnic self-identification is touched upon. The intermediate results of the research reflect both universal and unique (ethnic, group) adaptive forms of ethnic entrepreneurship manifestations and its importance for the preservation of historical and cultural heritage.